Contact and bending fatigue behaviour of austempered ductile iron gears. (March 2018) - Gorla, Carlo; Conrado, Edoardo; Rosa, Francesco; Concli, Franco
In the present paper a research programme aimed at investigating both the bending and contact fatigue properties of an austempered ductile iron applied to gears is presented, in order to determine reliable values of the limits, which take into account the influence of the production process, to be applied in the design of gearboxes. The bending fatigue tests are performed according to the single tooth fatigue approach and the pitting tests are performed with a back-to-back rig. Metallurgical analysis is performed on the failed specimens, in order to understand the origin and the propagation of the failures and to appreciate the influence of the micro-structure on the performances obtained.